2018
DOI: 10.1111/jerd.12436
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electronic cigarettes on dental enamel color

Abstract: Objective: The use of electronic cigarettes (ECIGs) has recently increased as an alternative to conventional smoking tobacco products. The literature is scarce on the effects of ECIGs on dental and oral structures. Therefore, the objective of this study was to observe whether ECIG aerosol could alter the color of dental enamel.Materials and methods: Sixty-three bovine enamel specimens were randomly separated into groups (n = 7) and treated with aerosols with different e-liquid flavors (neutral, menthol, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…14 As a result, it has the potential to become an epidemic. 15 A common known side effect of ENDS is the discoloration of teeth, 11 however its effect on oral restorations is not reported. CIELab system was employed for discoloration assessment, as it relates to clinical significance and compares difference in measurements to subjective observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 As a result, it has the potential to become an epidemic. 15 A common known side effect of ENDS is the discoloration of teeth, 11 however its effect on oral restorations is not reported. CIELab system was employed for discoloration assessment, as it relates to clinical significance and compares difference in measurements to subjective observations.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Pintado-Palomino et al, exposure of teeth to ENDS aerosol resulted in ΔE range from 1.9 to 4.6, these findings are similar to the present study in relation to ceramic specimens. 11 Cigarette smoking results in combustion of elements resulting in release of metals like arsenic, lead and cadmium along with dark components of smoke. These elements deposit on the surface, resulting in discoloration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other oral side effects attributed to e‐cigarette use are nicotine stomatitis, black hairy tongue, angular cheilitis and xerostomia with the latter being the most common 8 . E‐cigarette vapour also seems to alter enamel colour and especially, the menthol and tobacco e‐liquids reduce the yellowness of the enamel compared to neutral e‐liquid 13 . On the other hand, e‐cigarette inhalation has also been shown to contribute to periodontal disease and thus has a negative impact on periodontal health and dental implants 15,16,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a widespread misconception that ENDS are a harmless substitute for conventional cigarettes, the possible immediate and long‐term risks are yet not fully documented. Recently, several in vivo and in vitro studies have demonstrated a variety of oral and systemic adverse effects after the inhalation of the ENDS aerosol from both nicotine and nicotine‐free devices 13‐18 .…”
Section: Introductionmentioning
confidence: 99%